Workshop Penggunaan Aplikasi Google Meet Sebagai Pendukung Kegiatan Mengajar Bagi Guru Di Kecamatan Kampar - Afriza Rahma Rani; Romi Laspita; Nasrul Nasrul; Yolanda Pahrul (Jurnal Pengabdian Masyarakat (ABDIRA), 2023)
Current teaching and learning activities must be supported by utilizing Google Meet. The purpose of this service is to train teachers to have the skills to utilize Google Meet in learning, assist teachers in designing learning and instructions on the learning and teaching process using Google Meet and teachers are able to make optimal use of the digital era to support the learning process. The service method is carried out at SDN in Kampar District.